Consideration of Intestinal Parasite in Day-Care Center Children in Karaj City in 2012 - F. Haji Aliani; S. Einipor; A. Abadi; F. Tahvildar Bidrouni (Bihdād, 2014)
History and Aim: Parasitical Diseases are the most important economic- health problems of most developing countries. Children who belong to very important constituents of society are at risk of such diseases. The parasitic transmission in some places with children come together has a very special importance because they interact closely to each others. Constant and regular study in developing countries for planning to control these diseases is essential. Thus, the present study aims to explore the prevalence of parasites and enterobius and effective factors in their spread among children of Karaj kindergartens in 1391. Materials and Methods: This is a descriptive study and sampling was random clustering from34 kindergartens out of 154 active kindergartens of 9 districts of Karaj city under supervision of state welfare organization of Karaj using a random number table. In this project the prevalence of enterobius and other intestinal parasites in 904 children from one to six years old in Karaj in 2o13 was studied. The number of samples was calculated using 95% confidence interval and relative accuracy of 35% and hypothetical prevalence of 5% of intestinal parasites to be 596. Considering 50% efficacy for clustering method, increased the sample size to 894. The questionnaires collecting the required data like age and gender of the child, and were used for gender, age, occupation and education of the parents and effective factors on infection with intestinal parasites like hand washing and using personal drinking glass and clinical symptoms in children and symptoms reported by the child to his/her parents or caregiver and the demographic data. The results of the scotch test, either positive or negative, were recorded. Formalin ether and direct smear test were performed on three samples of every case which collected for find determination inconsecutively. For the eneterobius diagnosis, the scotch test which is more specific was used. Results: A totally of 904 samples were collected which 460 of them (50.9%) were male and 444 (49.1%) were female. The prevalence of intestinal parasite infection with formalin ether test was 16.7% and in Scotch tape test for Enterobius vermicularis was 2.3%. The most common protozoan was Blastocystis hominis in 84 children (9.3%) and Giardia in 66 children (7.3%). Additionally, infection with Endolimax nana was reported in 3 children (0.3%) and Entamoeba histolitica was reported in 4 children (0.4%). In this study there was a significant correlation between intestinal parasite and children’s age and also the way that vegetables were washed. Conclusion: According our results, the prevalence of intestinal parasites especially Giardia and Blastocystis in kindergartens of Karaj is high. This can be due to the lack of awareness of parents and children about the modes of transmission and Untreated infected persons and carriers that serve as carriers know. Health education to children, teachers and parents and six-month trial for child care staff and cure of infected people is effective in reducing the transmission of infection. Overall, poor personal hygiene, transmission of infection from mother to children and from child to other children are effective in persistence of the disease. Therefore high education of children, caregivers and parents and effective treatment of infected people are keys to reduce the rate of infection and transmission.